Optimalisasi Pengambilan Keputusan Pemasaran melalui Analisis Data Analytics di Patra Cirebon Hotel & Convention - I Gusti Made Juniarta; Aletta Dewi Maria Th (Mahesa Research Center, 2024)
This article aims to analyze the role of data analytics in optimizing marketing strategies at Patra Cirebon Hotel & Convention, particularly in enhancing service personalization and the effectiveness of marketing campaigns. Using the theoretical approach of digital marketing management and customer-based data analysis, this study collected data through interviews with the marketing manager and secondary data analysis of the hotels performance reports, which were then qualitatively analyzed. The study results indicate that data analytics contributes significantly to increasing sales conversion and customer loyalty through more targeted personalization strategies. However, this research also reveals several challenges, such as limited human resources and the complexity of integrating data from various sources. Nevertheless, these findings are relevant for marketing practices in the hospitality sector, offering hotel managers guidance on leveraging data analytics to drive business growth. This research is expected to serve as a reference for marketing practitioners in the hospitality industry, particularly in designing data-driven strategies that are more efficient and customer-focused, as well as adding value to the development of customer-oriented marketing practices.